An exploration into key roles in making project-based learning happen: Insights from a case study of a university. Issue 1 (13th April 2020) - Pan, Gary; Seow, Poh-Sun; Shankararaman, Venky; Koh, Kevin
Abstract : Purpose: One of the main obstacles facing project-based learning (PBL) adoption relates to a lack of understanding by teachers and students in the roles they are required to play in the learning process. This study aims to address this obstacle, so as to better promote regular adoption of PBL pedagogy in educational institutions. Design/methodology/approach: The strategy was to undertake an in-depth case study of PBL courses taught in UNI-X's undergraduate curriculum. The case study approach is particularly appropriate for this exploratory study because it allows to capture the organizational dynamics of the phenomenon better and also its ability to explain the phenomenon based on interpretation of data. Findings: This paper presents an empirical study on the role perspective of PBL in a collaborative project environment. By drawing upon a case study of UNI-X, the authors argue that a teacher plays the roles of a designer, champion, facilitator and manager in a PBL course. To ensure that learning is effective, students should play the roles of a self-directed learner and a warrior when completing their projects. It is clear that role ambiguity and role conflict could occur in PBL courses and might even impact the effectiveness of student learning. Originality/value: For researchers, this paper contributes to the PBL literature by introducing a role perspective of PBL. This study identifies a list of roles a teacher and a student could potentially play in a PBL setting. Such understanding could serve as a reminder for a teacher and a student for the roles they need to play in achieving learning outcomes of a PBL course.